Memahami Pemikiran Karya Charles Kimball When Religion Becomes Evil : Five Warning Signs (2008)1 Agama Menjadi Sumber Bencana Kejahatan - Muhammad Husni (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Kimball's not so comprehensive writing underscores the downside of religion. His writings seem unbalanced, in the sense of not showing the reverse side of the five alarms elaborated. Kimball actually from the beginning was aware that his study in this book is not comprehensive. However, his main purpose in writing this book is not to present a comprehensive study of the not only complex phenomenon and mutiwajah, but